PSXV-27 Late-Breaking: Evaluation of antioxidant capacity in receiving beef calves challenged with lipopolysaccharide (LPS). (8th October 2021) - Barker, Samantha N; Jackson, Treylr; Richeson, John; Carroll, Jeff A; Burdick-Sanchez, Nicole C; Broadway, Paul R; Legako, Jerrad F
Abstract: The objective of this study was to evaluate antioxidant capacity in plasma of beef calves challenged with LPS. Following an initial feeding period of 40 d, steers (n = 32; 379 kg ± 30.7) were transported to the Livestock Issues Research Unit's Bovine Immunology Research and Development Complex and challenged intravenously with LPS (0.25 µg/kg BW) on d 41. Blood samples were collected via jugular catheter at -2, 0, 2, 4, 6, 8, 10, 12, 18, 24, 36 and 48 h relative to the LPS challenge at 0 h. Blood samples were processed to isolate plasma for indicators of oxidative stress with a colorimetric assay to determine ferric reducing antioxidant power (FRAP) values via concentration of ferrous iron (µM). Data were analyzed as repeated measures using the GLIMMIX procedure of SAS. Antioxidant values did vary with time (P < 0.001) being greater (P < 0.05) at -2, 0, 2, 36, and 48 h. Antioxidant capacity was reduced at 6 and 8 h (P < 0.05), with the least FRAP value observed at 8 h post-challenge. Antioxidant capacity increased (P < 0.05) again at 10 h, showing similar (P > 0.05) concentrations to those observed at 4 h. By 24 h post-challenge, plasma FRAP values increased (P < 0.05) similar to initial values at -2, 0, and 2 h. It can be inferred that oxidative stress contributes to reduced antioxidant capacity, ultimately interfering with animal growth and productivity. While these values reflect the oxidative stress response to an acute endotoxin challenge, and a subsequent recovery returning to homeostasis within 24 to 48 h, they may also correlate with other physiological and immunological indicators associated with an acute endotoxin challenge.